The impact of large-scale sports events on national identity: a structural equation model based on the residents' perspective - Jing Wang; Zhiyi He; Yijuan Lu (Frontiers in Sports and Active Living)
IntroductionLarge-scale sports events have a profound impact on the enhancement of residents' national identity. The study takes the Hangzhou Asian Games as an opportunity to investigate the influence of such events on national identity and the underlying factors.MethodsThe study takes the impact of residents' involvement in the Asian Games on their national identity as the research object, constructs a theoretical model with subjective well-being and city image as the mediator variables, randomly selects 1,096 residents by questionnaire survey, and analyzes their interrelationships as well as deeper influencing factors by using structural equation modeling and bootstrap.ResultsThe results show that the involvement of Hangzhou residents in the Asian Games has a significant positive impact on national identity, subjective well-being and city image (Estimate = 0.237/0.287/0.3). Furthermore, subjective well-being and city image have a significant positive impact on national identity (Estimate = 0.321/0.141), and city image has a significant positive effect on subjective well-being (Estimate = 0.264).DiscussionIt can be concluded that the degree of involvement in major sports events has a direct positive effect on national identity, and subjective well-being and city image play a partially mediating role in this effect. The results of the study provide a resident's perspective for assessing the impact of large-scale sports events, and provide elements that can be used as a reference for governments, city planners and event organizers to assess large-scale sports events.